Utilization of Lapindo Volcanic Mud for Enhanced Sono-sorption Removal of Acid Orange 52 - Nur Hidayatul Nazirah Kamarudin; Herma Dina Setiabudi; Aishah Abdul Jalil; Siti Hazirah Adam; Nur Fatien Muhamad Salleh (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
This study applied ultrasonic irradiation technique to remove acid orange 52 (AO52) and in the meantime utilizing the potential adsorbent, Lapindo volcanic mud (LVM). LVM was collected from the erupted mud in Sidoarjo, Indonesia and calcined prior the adsorption process. Previously in another study, Lapindo was proven to be efficient for adsorption of dyes in single adsorption method. In this study, the combination of adsorption with ultrasound, or as known as sono-sorption shows that the adsorptivity increased from 95.54 mg/g to 129.5 mg/g. The isotherm study shows that this process obeyed Langmuir isotherm model with adsorption capacity of 833.33 mg/g. The enhancement of sono-sorption method as compared to conventional method is believed to be resulted from the facilitated mass transfer driven by the ultrasound, along with the adsorption ability of LVM. The kinetic study fit to the pseudo second order equation.